2008
DOI: 10.1089/cap.2007.0039
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Effects of Multilayer-Release Methylphenidate in the Treatment of Children with Attention-Deficit/Hyperactivity Disorder

Abstract: Objective: The aim of this study was to compare the pharmacodynamics of a new multilayerrelease (MLR) formulation methylphenidate (MPH; Biphentin ® ) with immediate-release (IR) MPH (Ritalin ® ) in a double-blind, cross-over, placebo-controlled study in patients with attention-deficit/hyperactivity disorder (ADHD). Conclusions: MLR MPH given once daily produces equivalent improvements in behavioral and cognitive measures, and has a duration of effect at least as long as that of IR MPH given twice daily. 11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…This patient-reported amelioration was supported by the significant improvement reported by knowledgeable informants; for the other secondary cognitive end point, a performance-based computerized test of neurocognitive function, the improvement seen with LDX was not statistically superior to placebo. Overall, these findings support previous evidence of the ability of dopaminergic agents to mitigate cognitive dysfunction (Killgore et al, 2008;Schachar et al, 2008). However, because there are typically only modest correlations between BRIEF-A and performance-based measures of executive function , this finding is not surprising.…”
Section: Discussionsupporting
confidence: 86%
“…This patient-reported amelioration was supported by the significant improvement reported by knowledgeable informants; for the other secondary cognitive end point, a performance-based computerized test of neurocognitive function, the improvement seen with LDX was not statistically superior to placebo. Overall, these findings support previous evidence of the ability of dopaminergic agents to mitigate cognitive dysfunction (Killgore et al, 2008;Schachar et al, 2008). However, because there are typically only modest correlations between BRIEF-A and performance-based measures of executive function , this finding is not surprising.…”
Section: Discussionsupporting
confidence: 86%
“…After morning administration of MPH-MLR, a small drop in plasma MPH concentration occurs *4 hours postdosing, followed by a gradual increase in MPH concentrations, producing a second attenuated peak at *7 hours after dosing and then a gradual decline throughout the evening and nighttime hours (Adjei et al 2014a,b). Phase 2 studies of MPH-MLR in children, adolescents, and adults across a variety of settings demonstrated that once-daily administration produces significant improvements in behavioral and cognitive measures Weiss et al 2007;Schachar et al 2008). The MPH-MLR capsule is ingested orally or opened for its contents to be sprinkled on food; the two administration modes are bioequivalent (Adjei et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Multilayer-release (MLR ® ) MPH (Biphentin ® ) is a once-daily MLR bead formulation with a rapid rise in plasma levels after oral administration and an onset of action within 1 hour (Purdue Pharma Canada 2006; Schachar et al 2007) that has previously been shown to reduce ADHD symptoms in adults (Jain et al 2007). In single-dose pharmacokinetic studies, in young, healthy adults and children with ADHD, this controlled-release MLR formulation was fully bioavailable relative to the IR formulation, with a relative area under the plasma concentrationtime curve of approximately 100% over the total 24-hour dosing interval and 70-75% over the period corresponding to the duration of a typical school day (Quinn et al 2007).…”
Section: Introductionmentioning
confidence: 99%